Paranoia and negative schema about the self and others: A systematic review and meta-analysis. (December 2021) - Humphrey, Charlotte; Bucci, Sandra; Varese, Filippo; Degnan, Amy; Berry, Katherine
Abstract: Negative self and negative other schema have been implicated in the development of paranoia. The current study provides a meta-analysis, narrative review and quality appraisal of quantitative studies investigating the relationship between negative self and negative other schema and paranoia across the paranoia continuum. A systematic search identified 43 eligible studies; 25 were included in the meta-analysis. Meta-analytic findings demonstrated a medium to large relationship between paranoia and negative self-schema ( r  = 0.46, 95% CI 0.39 to 0.53) and negative other schema ( r  = 0.48, 95% CI 0.38 to 0.56). The magnitude of associations was similar across people with and without psychosis. Findings demonstrated that associations between negative self-schema and paranoia were not always statistically significant when controlling for confounding variables, particularly depression. The association between negative other schema and paranoia tended to remain significant when controlling for confounding variables. Findings also demonstrated that negative schema may mediate relationships between adverse experiences in childhood and paranoia. Overall, findings support theoretical proposals that both negative self and negative other schema are associated with paranoia. Longitudinal studies are required to confirm the direction of effects. Findings provide support for incorporating and targeting negative self and negative other schema in psychological formulations and therapeutic work. Highlights: There is a medium to large association between negative self-schema and paranoia. There is a medium to large association between negative other schema and paranoia. Depression may account for associations between negative self-schema and paranoia. Negative schema may mediate relationships between childhood adversity and paranoia. Further longitudinal studies are needed to determine the direction of effects.